Immunosuppressive Immature Myeloid Cell Generation Is Controlled by Glutamine Metabolism in Human Cancer - Wu, Wen-Chao; Sun, Hong-Wei; Chen, Jing; OuYang, Han-Yue; Yu, Xing-Juan; Chen, Hai-Tian; Shuang, Ze-Yu; Shi, Ming; Wang, Zilian; Zheng, Limin (Cancer immunology research, 2019)
Tumor-associated myeloid cells are one of the prominent components of solid tumors, serving as major immune regulators for the tumor microenvironment (TME) and an obstacle for immune-checkpoint blocking (ICB) therapy. However, it remains unclear how metabolic processes regulate the generation of suppressive myeloid cells in the TME. Here, we found that hematopoietic precursor cells are enriched in the tissues of several types of human cancer and can differentiate into immature myeloid cells (IMC). Tumor-infiltrating IMCs are highly immunosuppressive, glycolytic, and proliferative, as indicated by high levels of M-CSFR, Glut1, and Ki67. To elucidate the role of metabolism in regulating the generation of IMCs, we induced suppressive IMCs from hematopoietic precursor cells with GM-CSF and G-CSF We found that the generation of suppressive IMCs was accompanied by increased glycolysis, but not affected by glucose deprivation due to alternative catabolism. Generation of IMCs relied on glutaminolysis, regardless of glucose availability. Glutamine metabolism not only supported the expansion of IMCs with glutamine-derived α-ketoglutarate but also regulated the suppressive capacity through the glutamate-NMDA receptor axis. Moreover, inhibition of glutaminase GLS1 enhanced the therapeutic efficacy of anti-PD-L1 treatment, with reduced arginase 1 myeloid cells, increased CD8 , IFNγ and granzyme B T cells, and delayed tumor growth in an ICB-resistant mouse model. Our work identified a novel regulatory mechanism of glutamine metabolism in controlling the generation of suppressive IMCs in the TME.